Pengaruh Pembelajaran Daring dengan Google Classroom terhadap Prestasi Belajar Fiqih Siswa Kelas XI Madrasah Aliyah Abu Darrin Bojonegoro - Ida Fauziatun Nisa; Farida Isroani (Jurnal Bahastra, 2020)
Constraints sometimes encountered by teachers in using the Google Classroom application are students' internet networks that are less stable, so students cannot take online learning according to a predetermined schedule and the limited number of data quotas they have when they want to take online learning, so that not a few are forced to late in submitting assignments through the application. This study aims 1) To determine online learning with Google Classroom in class XI Madrasah Aliyah Abu Darrin Bojonegoro, 2) To determine Fiqh learning achievement of class XI Madrasah Aliyah Abu Darrin Bojonegoro students, 3) To find out how online learning with Google Classroom has an effect on the learning achievement of Fiqh students of class XI Madrasah Aliyah Abu Darrin Bojonegoro. This research is a survey research with a quantitative approach. The data analysis technique used simple linear regression analysis. The research sample, namely students of class XI.2 IPA, totaling 31 students. The results showed that 1) Online learning with Google Classroom for class XI was quite adequate, 2) Fiqh learning achievement for class XI was quite adequate, 3) Online learning with Google Classroom had a negative effect on Fiqh learning achievement of class XI Madrasah Aliyah Abu Darrin Bojonegoro students.